Homogeneización de las series temporales de viento en las estaciones meteorológicas de la provincia de Loja. - Tenechagua Ayora, Luis Alberto (2015)
This present research has as purpose to get full details of wind, determine the normality, obtain the correlations between stations and homogenization of all series of wind weather stations in the province, to know the potential of this resource which has the province. The study was carried out with the data obtained from INAMHI, La Algeria stations, Saraguro, Malacatos, Quinara, Cariamanga, Yangana, Celica, Gonzanamá, Amaluza and Zapotillo, since they have a greater amount of data that have been collected from 1982 to 2010. The data obtained from wind series contain gaps in the collection, which were filled with the linear equation obtained from the data provided by INAMHI. The normal distribution of the stations were performed by Chi-square Jarquer-Bera tets, The correlations were done using the statgraphics program. Through Statgraphics was made multiple homogenization of correlations with an independent variable of the month which is needed to calculate, obtaining in this way a greater reliability data than 90%